The Effect of P4S Porang Kepel’s Role on the Sustainability of Porang Farming in Kare District, Madiun - Beta R. Setiawati (Interdisciplinary Social Studies, 2026)
Porang is a leading commodity with export potential that is widely cultivated in Madiun District. The success story of farmers in cultivating porang led to the inauguration of the Pusat Pelatihan Pertanian dan Perdesaan Swadaya (P4S) Porang Kepel in Kare Subdistrict to support efforts to develop and sustain porang farming in Madiun District. The purpose of this study was to understand the role of P4S Porang Kepel in providing training that influences farmers' internal characteristics and the sustainability of porang farming through an approach using path analysis. This research employs a quantitative approach using path analysis with Structural Equation Modeling (SEM) to examine the relationships between P4S roles (as a learning group, facilitator, and consultant) and the three dimensions of farming sustainability: economic, physical environmental, and social. The role of P4S Porang Kepel as a study group has a direct negative influence on the physical environment aspects of sustainability and a negative indirect effect on the economic and social aspects, with the physical environment as an intervening variable. In contrast, the role of P4S Porang Kepel has a positive indirect effect on the social aspect of sustainability through the intervening variable of attitude toward porang farming. These different types of influence stem from the role of P4S as a study group, along with information from traders, which created cognitive dissonance for farmers in assessing the sustainability of porang farming.